2012
DOI: 10.1111/j.1525-1446.2012.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Self‐efficacy Scale for Preventing Early Childhood Diarrhea: Validity and Reliability

Abstract: The scale was found reliable. Cultural adjustments may be needed to extrapolate the scale to other endemic areas worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
2
27
0
5
Order By: Relevance
“…This conduct has been observed in other studies in the instrument validation field (17)(18) . A correlation was observed between the self-efficacy levels of parents/guardians and their degree of education (p = 0.001), attesting the first hypothesis of contrasted groups, which stated that people with more than nine years of formal education present higher self-efficacy scores.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This conduct has been observed in other studies in the instrument validation field (17)(18) . A correlation was observed between the self-efficacy levels of parents/guardians and their degree of education (p = 0.001), attesting the first hypothesis of contrasted groups, which stated that people with more than nine years of formal education present higher self-efficacy scores.…”
Section: Discussionsupporting
confidence: 81%
“…Asthma control poses specific challenges and can be influenced, to some extent, by self-efficacy. Reinforcing it in parents, guardians, and patients has the potential to improve the capacity of self-management of chronic illnesses, especially childhood asthma (17) . A study carried out in Florida, United States (30) , concluded that parents with a high perceived selfefficacy also showed better results in control parameters of the disease, corroborating the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…11 The collected data were organized and analyzed by means of the StatisticalPackage for the Social Sciences -SPSS (version 20.0) program, comparative statistical analysis using Pearson's Chi-square tests, linear association by linear and likelihood ratio, establishing a level of significance of less than 5%. It was opted to use the median as a parameter of division between the results from the Kolmogorov-Smirnov test.…”
Section: Maternal Knowledge For Prevention Of Childhood Diarrheamentioning
confidence: 99%
“…Modifications of expressions and response patterns also occurred in other instrument adaptations [8,9].…”
Section: Discussionmentioning
confidence: 99%